2014
DOI: 10.1002/biot.201400172
|View full text |Cite
|
Sign up to set email alerts
|

An improved ARS2‐derived nuclear reporter enhances the efficiency and ease of genetic engineering in Chlamydomonas

Abstract: The model alga Chlamydomonas reinhardtii has been used to pioneer genetic engineering techniques for high-value protein and biofuel production from algae. To date, most studies of transgenic Chlamydomonas have utilized the chloroplast genome due to its ease of engineering, with a sizeable suite of reporters and well-characterized expression constructs. The advanced manipulation of algal nuclear genomes has been hampered by limited strong expression cassettes, and a lack of high-throughput reporters. We have im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…Statistical significance was accepted at P , 0.05. Primary screening data were analyzed using HCS-Analyzer, an open-source application for high-content screening (Specht et al, 2015), and chemoinformatics analysis was done using the Bioconductor Chemmine R package (Schaffer, 2003) or Tibco Spotfire Lead Discovery. Structural rendering of the compounds was done using the ChemDraw Professional 14 suite (PerkinElmer).…”
Section: Statistical Assessment and Chemoinformatics Analysis Of Compmentioning
confidence: 99%
“…Statistical significance was accepted at P , 0.05. Primary screening data were analyzed using HCS-Analyzer, an open-source application for high-content screening (Specht et al, 2015), and chemoinformatics analysis was done using the Bioconductor Chemmine R package (Schaffer, 2003) or Tibco Spotfire Lead Discovery. Structural rendering of the compounds was done using the ChemDraw Professional 14 suite (PerkinElmer).…”
Section: Statistical Assessment and Chemoinformatics Analysis Of Compmentioning
confidence: 99%
“…Synthetic promoters were cloned with the RBCS2 5'UTR, which was amplified with appropriate primers to allow 15 bp overhangs with the synthetic promoters as well the digested backbone (Table S8), resulting in the constructs in Figure 1b. To rearrange sap11 with the hygromycin cassette downstream of the mCherry cassette, each half of pBR4 was amplified with appropriate primers for USER cloning into the HCR1, a modified pBlueScript II (Agilent, Santa Clara, CA), as previously described (Specht et al, 2015) (Table S8). The rearranged construct was then digested with NdeI and XbaI to remove ar1 and replace it with sap11 which was PCR amplified and SliCE cloned into the rearranged pBR4.…”
Section: Plasmid Constructionmentioning
confidence: 99%
“…Potential reasons are biased codon usage ), epigenetic transgene silencing (Cerutti et al 1997), positional effects and chromatin structure (Specht et al 2014;Strenkert et al 2011), aberrant processing, lack of suitable regulatory sequences, or potentially further currently unknown mechanisms (Fuhrmann et al 1999). Efficient transgene expression strongly relies on non-coding, cis-acting elements (Barnes et al 2005;Lumbreras et al 1998;Sizova et al 2001), and several elements promoting stable transgene expression have been identified.…”
Section: Tools and Techniques For Endogenous And Exogenous Gene Exprementioning
confidence: 99%
“…For this reason, we selected this hybrid system to develop a versatile, modular vector tool for nuclear encoded recombinant protein production (Lauersen et al 2013;Lauersen et al 2015). A 1425-bp promoter/5′-UTR region upstream of the endogenous ARG7 gene was recently demonstrated to convey promoter activity of similar strength as the hybrid HSP70A-RBCS2 promoter in the context of an ARS2 reporter assay (Specht et al 2014), therefore representing an interesting alternative. Promoter trapping (Haring and Beck 1997) has also been performed and led to the identification of several efficient regulatory promoter sequences (Vila et al 2012).…”
Section: Promotersmentioning
confidence: 99%